1977
DOI: 10.1242/jeb.66.1.65
|View full text |Cite
|
Sign up to set email alerts
|

The mauthner-initiated startle response in teleost fish

Abstract: 1. A characteristic behaviour, the ‘Mauthner-initiated startle response’, was recorded and quantitatively analysed with high-speed cinematography (200 frames/sec) after vibrational stimulation in 11 of 13 teleost species which possess Mauthner cells. 2. The latency of the response is 5–10 msec. This behaviour has: (a) an initial phase, the ‘fast-body-bend’, lasting about 20 msec and consisting of a stereotyped displacement of the head and tail to one side and (b), a second phase, the ‘return-flip’, consisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 433 publications
(46 citation statements)
references
References 13 publications
0
45
0
1
Order By: Relevance
“…A recent study demonstrated that wild-type zebrafish larvae exhibit a classic habituation response to multiple acoustic/tap stimuli by 5dpf 14 , reinforcing previous work from the 1970s that first used zebrafish to study this basic form of learning 44 , 45 . As an initial assessment of higher circuit development in our mutant lines, we tested their habituation response to series of acoustic taps at 7dpf (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…A recent study demonstrated that wild-type zebrafish larvae exhibit a classic habituation response to multiple acoustic/tap stimuli by 5dpf 14 , reinforcing previous work from the 1970s that first used zebrafish to study this basic form of learning 44 , 45 . As an initial assessment of higher circuit development in our mutant lines, we tested their habituation response to series of acoustic taps at 7dpf (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…We used AV stimulation via pressure-application of aCSF in the otic vesicle to induce stereotypical escape responses (Böhm et al, 2016;Lacoste et al, 2015;Pantoja et al, 2017). In freely-swimming and free-tailed fish, AV stimuli induce an escape response starting with a fast and powerful contralateral C-bend relying on motor neurons to move away from the threat (Domenici & Hale, 2019;Eaton et al, 1977;Eaton et al, 1991, Eaton et al, 1981. In agar-restrained larval zebrafish, AV stimulation elicited a bilateral contraction of the tail typically lasting more than 1 s after the stimulus (Figure 1a, Movie S1), likely reflecting a C-bend followed by a struggle.…”
Section: Av Stimuli Elicit a Calcium Wave In Radial Astrocytes Starting In The Rostral Spinal Cordmentioning
confidence: 99%
“…Because acoustic and light responses are either absent or less robust at these early developmental stages, light touch was used to induce escape response swimming behavior. At both 48 and 96 hpf, larvae respond to light touch to the head with a well-characterized C-start, which consists of an initial C-shaped body bend to reorient the animal away from the touch stimulus, followed by loweramplitude body undulations that propel it several body lengths away (Eaton et al 1977;Granato et al 1996;O'Malley et al 1996;Eaton et al 2001;Kohashi et al 2012). After PTZ exposure, hyperactive behavior is observed, and two prominent aspects of swimming performance are altered similar to older fish: larvae performed longer duration escape responses and these responses are interspersed with multiple C-shaped body bends (Figure 1; Supplementary Movies 1 and 2).…”
Section: Gabaa Receptors Control Early Larval Swimming Behaviormentioning
confidence: 99%